(untitled) (Academic Journal of Internal Affairs, 2020)
The Still Image Facial Recognition System has been in operation for four years in Hungary. The present study details the experiences gained to date, as well as the possibilities, results and plans related to the subject. It briefly presents the history of still image face recognition, provides international outlook, describes the legal framework and the operation of the system, and finally outlines future development opportunities.